The Meaning of Longing for the Tradition of “Ngirup Cuko Pempek” Palembang as Friendship Communication in the Covid–19 Pandemic Era - Isnawijayani Isnawijayani; Agustin Rozalena; Ratu Mutialela Caropeboka (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This research aimed to construct the meaning of longing for the tradition of ngirup cuko pempek as a friendship communication for the people of Palembang in the Covid-19 pandemic era. This longing communication research is qualitative one. The object of research, namely the behaviour of longing for tradition ngirup cuko pempek. The research subjects are Palembang residents who often travel out of town. The research data used participated observation, interview and documents analysis obtained from informants. The data analysis technique used an interactive model of Miles and Huberman. The results of the research showed, 1) Ngirup cuko is the local wisdom and eating culture of Palembang citizens; 2) The meaning on the longing philosophy on ngirup cuko pempek shows love for the traditions identity of the region, kinship and togetherness, the friendship, as well as typically Palembang culinary promotion.